A new genus and species of the leafhopper subtribe Paraboloponina from China (Hemiptera, Cicadellidae) - Qu, Ling; Webb, M. D.; Dai, Ren-Huai (Zootaxa, 2015)
A new leafhopper genus and species Forficus maculatus Qu gen. nov., sp. nov. of the subtribe Paraboloponina (Deltocephalinae, Drabescini) are described from China. A checklist to the Paraboloponina from China is given and a key to genera is provided.